PENYEBAB QUALITY COST DAN PRODUCTIVITY, PABRIKAN HONDA DI AMERIKA SERIKAT RECALL BERAGAM SEPEDA MOTOR MERK HONDA - Moh. Asra (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
The Honda motorcycle company in America is being hit by a failure of a bigbike product called the Honda Monkey, around 44 units of the unit has become a defective item that must be recalled because there is a problem in the luggage rack that is vulnerable to breakage and cause an explosion because it is located next to the tank. This motorbike is not marketable, so from Honda filed a product recall. Aside from the side, the susceptibility of the breakage of the luggage rack damages the electrical stability of the battery. In addition, there are also problems with relay relay starter button. Therefore, the factory directly contacted the customer who owns the motorcycle. So that there are no accidents or accidents due to defects in Honda's bicycle products. Based on this case, to respond and discuss using cost quality and productivity in the decision-making accounting used by companies and business people worldwide. Quality cost is an event that includes costs caused by low quality. In the quality of products for cost quality there are several components of reliability, performance, easy maintenance, features, durability / strength, aesthetics, comfort and compatibility. But not only that, it also requires a cost quality measurement approach and a quality approach vs. the productivity of an item to be bought and sold. Therefore, the author will discuss and explore the issue "The Causes of Quality Cost and Productivity, Honda Manufacturers in the United States Recall a variety of Honda motorcycles" Keywords: Quality Cost and Productivity, recall, Honda motorcycle brand.